The Structure of Lanny Oral Literature: A Critical View - Manase H Halitopo; Napius Kogoya (Universitas Kapuas, 2024)
Oral literature is a cultural expression that verbally transmits values from one generation to the next among the community supporters. This oral literature research aims at (1) presenting the stories' plots through the research's primary goal, 2) introducing the characters that appear in the story, (3) outlining the characters in the stories, (4) recognizing and explaining the settings of the stories, and 5) recognizing and defining symbols in the stories based on Yektingtyas's points of view (2016). The approach in this research incorporates literary criticism into secondary and primary qualitative data combined throughout the data collection process. The primary data were analyzed thoroughly, while the secondary data were utilized as references to analyze the primary data. The results show that Ilik was born to a mother under the shade without a father. Initially, the narrative focused solely on the character's day-to-day activities. The folks washing the pig gut rope cast away and flung the dog with the stone when he tried to devour the remaining portion. The pregnant woman and her children arrived in the village the following day to cook the raw pork they had managed to rescue. The portrait of this literary work depicts the characters’ lives and social harmony, allowing them to nurture indigenous values while learning to explore more life lessons from society.